An Online Poetry Laboratory Project : : Creation and consumption of Thai digital poetry - Ployhirun, Natruethai; Boonkhachorn, Trisilpa (Journal of Letters, 2022)
This article is a part of a Ph.D. thesis titled “Digital Poetry in the Thai Social Context (2012 – 2021).” In terms of creating and reading literature, digital media is the new choice for Thai writers and readers. How will Thai poets and poetry be transferred to and created in these digital spaces? The project “Poetry on the Cloud” is an experimental laboratory aiming to open a space for creativity and poetry on online media by hosting 10 forums. This study found that digital poetry area and online poetry reading events are a new way for poets to quickly reach large audiences, allowing readers to read simultaneously with poets reading their own poems aloud, an aspect of the artform that online media are helping to revive. There is also creative coordination with various arts, both performance and music, adding to the enjoyment of poetry. The content of the online poetry reveals the attitude of Thai poets towards poetry in the digital age. Poetry continues to be a form of expressing emotion and recording people’s lives and Thai society in the era of globalization and digital society. The project has also opened up a space for poets to create works with readers or listeners as readers can collaborate with poets online to have greater access. It is a forum for exchanging knowledge between senior poets and the new generation as well as fostering poetry criticism.